Analisis Kelayakan Pembangunan Distribution Center Pada Perusahaan Bidang Pertanian - Resista Vikaliana, Vikaliana; Yelita Anggiane Iskandar; Carissa Rahmadani; Lailatul Fitriyani; Verina Marshaniswa; Natasya Sondang Panjaitan; Alfito Hudha (TIN: Terapan Informatika Nusantara, 2023)
PT Esa Sarwaguna Adinata is a company engaged in the agricultural sector that always strives to maintain the quality of its products, resulting in an increase in the number of demand points by twice the amount of the previous demand points. The addition of these demand points has caused the company to struggle to fulfill all demands. Therefore, PT Esa Sarwaguna aims to make an additional investment in the form of a distribution center to meet all demands. The purpose of this research is to test the feasibility of adding a distribution center to PT Esa Sarwaguna Adinata in fulfilling all demands. The testing is carried out using the Net Present Value (NPV), Payback Period, and Interest Rate of Return (IRR) methods. Based on the analysis of the processed data that has been conducted previously regarding feasibility, seen from technical aspects such as the feasibility of investing in adding a new distributor hub, the calculation is based on the Net Cash Flow (NCF) value held by PT Esa Sarwa Adinata, resulting in an Interest Rate of Return (IRR) value of 148%, and there will be a return in the first year based on the payback period calculation, which indicates that the investment in adding a new distributor hub at PT Esa Sarwa Adinata is feasible to be carried out